Changing welfare regimes in East and Southeast Asia: crisis, change and challenge - Croissant, Aurel (Social policy and administration, 2004)
The Asia-Pacific region is a latecomer to the development of the welfare state. However, in some countries, governments have implemented ambitious programmes to extend social security systems and to enlarge the institutional structure of their welfare states. Comparative study of the welfare systems in East and Southeast Asia is, however, underdeveloped and there still is a relative lack of accurate knowledge about welfare systems in the region. Since the Asian financial crisis, more attention has been paid to the social policies of the countries. This paper examines features of welfare regimes in Indonesia, Malaysia, the Philippines, Singapore, South Korea, Taiwan and Thailand, and undertakes a systematic review of the development, levels and patterns of welfare regimes in the region. Two core questions are answered: can the existing welfare systems help mitigate the social impact of the financial and economic crisis? What are the needs, challenges and developmental perspectives that inform the future of welfare regimes in this region?
Gesehen am 26.03.2021